Christian spirituality in South Africa - Kretzschmar, Louise; Kourie, Celia E. T. (Cluster Publications, 2001)
Spirituality is an area of increasing interest for humanity at this stage of history. The importance of spirituality in all areas of society is evidenced by workshops, conferences, retreats etc., held, in organisations e.g. of business, health-care, education, and political forums. The church and academia are re-assessing the value of training in spirituality, and new courses are meeting this need. With the foregoing in mind, the present book serves to locate Christian Spirituality in South Africa. In a country which is experiencing great political and social change, it is imperative that our new society be built on a strong foundation, formed by true gospel values. All the contributors write from their own experience of living and working in this country and are committed to the on-going development of the new South Africa. It is hoped that such an endeavour will be a 'call to rediscover our humanity in the presence of God and the Christian community, so that we may live as credible witnesses to God's kingdom in the context of a challenging and often broken world'.
Keywords: Africa; Christianity/Church History–1900-1999; Spiritual Life; Christian